General and inorganic chemistry - Bhidan Chandra Ray (New Central Book Agency, 2016)
This volume has been planned to do away with all these weaknesses. A new topic, namely antioxidants, has been included in 'Bioinorganic Chemistry' section to explore the origin of some fatal human diseases. In dealing with spectroscopy of compounds, the authors have tried to explain through vector representations of different microstate and Russel-Sanders' states derived from them.